Calculation of 20 kV Distribution Network Energy Losses and Minimizing Effort Using Network Reconfiguration in Region of PT PLN (Persero) UPJ Bantul - Slamet Suripto (Universitas Muhammadiyah Yogyakarta, 2017)
Power distribution system is a component of an electric power system to deliver electrical energy from substation to customer location. In power distribution system, there are some power loss was changed as heat. Power distribution losses is a natural occurrence, so one gets to be done only minimize to support global energy efficiency. The way to reduce power loss in the power distribution system is by reconfiguration the existing line. Reconfiguration means a process of operating the switch (NO and NC) and change the topology line. Then, power loss in the power distribution system is computed with “ETAP” simulation software. From computing result of distribution network losses on existing line at PT. PLN UPJ. Bantul BNL 6, BNL 7 and BNL 11 feeders are gotten energy losses as 2,669,328 kWh per year or 1.72 %. Network reconfiguration that involves BNL 6, BNL 7 and BNL 11 feeder gets energy losses decrease by 1.00 % per year.